A Linear Programming Formulation of the General Portfolio Selection Problem - Stone, Bernell K. (Journal of Financial and Quantitative Analysis, 1973)
Almost two decades ago, Markowitz [12] formulated the portfolio selection problem as a parametric quadratic programming problem. The crux of his formulation was the mean-variance assumption which asserted that a portfolio is efficient if (and only if): (1) it has less variance than any other feasible portfolio with the same return and (2) it has more return than any other feasible portfolio with the same variance.